2019
DOI: 10.1159/000501308
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Psychometric Properties of the Brazilian Version of the Montreal Cognitive Assessment as a Brief Screening Tool for Mild Cognitive Impairment and Alzheimer’s Disease in the Initial Stages in the Elderly

Abstract: <b><i>Objective:</i></b> To evaluate the applicability and the psychometric properties of Montreal Cognitive Assessment Brazilian Version (MoCA-BR) in the elderly, as well as comparing its accuracy as a tracking test for mild cognitive impairment (MCI) and mild Alzheimer’s disease (AD) with the accuracy of Mini-Mental State Examination (MMSE). <b><i>Method:</i></b> A transversal study was performed in 4 reference medical centers that care for the elderly. In all,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
1
12
0
1
Order By: Relevance
“…We could confirm the well-known findings that the educational level and age influence on both test scores, which indicate that the data used in the present study are comparable with data of many other studies in the field [9, 13, 20-22, 52, 53]. We could also confirm that older people score higher on the MMSE than MoCA probably because MoCA is more challenging, and lastly, we have shown that the rank correlation between the 2 tests is weak and that the scores cannot be used side by side.…”
Section: Discussionsupporting
confidence: 92%
“…We could confirm the well-known findings that the educational level and age influence on both test scores, which indicate that the data used in the present study are comparable with data of many other studies in the field [9, 13, 20-22, 52, 53]. We could also confirm that older people score higher on the MMSE than MoCA probably because MoCA is more challenging, and lastly, we have shown that the rank correlation between the 2 tests is weak and that the scores cannot be used side by side.…”
Section: Discussionsupporting
confidence: 92%
“…The guidelines indicate that the sensitivity of the MMSE is low when it is used alone ( 10 , 26 ). A transversal study of 229 elderly participants in four medical centers demonstrated that the MMSE has lower sensitivity than the MoCA ( 30 ). Three systematic reviews also demonstrated that the sensitivity and specificity of the MoCA are superior to those of the MMSE ( 29 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of significant differences between the comparison groups on a pragmatic questionnaire-based screening instrument for dementia, that is, the IQCODE, further ensured that the clinical cohort was free of subjects who had progressed to dementia. While the feasibility and convenience of using a single cognitive screening instrument such as ACE-III and MOCA for the diagnosis of MCI cannot be undermined [28-32], the drawback is that impairment on a single domain is common in MCI but may not be sufficient to impact the total score. Therefore, we did not rely on a single global screening instrument alone for diagnosis.…”
Section: Discussionmentioning
confidence: 99%